ANATOMICAL AND CLINICAL RELEVANCE OF SIRAVYADHA IN RELATION WITH MARMAS OF UPPER LIMB - S Syamlal,; Bhosgikar, Anup; Mulimani, N. G. (International Journal of Ayurveda and Pharma Research, 2015)
The science of Ayurveda is well recognized system of medicine which have unique specialty in the field of Shalyathanthra. The concepts of Ayurveda Shareera evolved 3000yrs ago. Because of generation gap concepts appear to be misinterpreted or not fully developed. At this junction it is our moral duty to take up such studies to understand the concepts clearly and to pass on knowledge to younger generation.It is one of the Para surgical procedure denoting letting of blood outside the body. Different modalities of Rakthamokshana are adopted according to Dosha avastha and Athura avastha. Siravyadha is one of the types of Rakthamokshana by Sasthravacharana. So as to explain its significance a stanza of Su.Sha 8/23 is sufficient.Acharya Sushrutha has given same importance of Dosha to Raktha also, where in many places he has classified many diseases as Rakthaja also. Siravyadha is often recommended as Shodhana chikitsa for such diseases. In the Sushruta Samhita Sharirastana 8th Chapter particular anatomical sites especially the Marma sthanas are recommended as anatomical landmarks for Siravyadhana in Particular diseases. So this study helps to explore the Anatomical & Clinical relevance of Siravyadha on the basis of available literatures. So a creative and logical approach has been done to locate Siras for Siravyadha in Particular disease with Pathophysiological interpretation. So it can be concluded that Siravyadha is effective modality of treatment in many diseases. So the study taken up here is Anatomical and Clinical Relevance of Siravyadha in Relation with Marmas of Upper Limb.